Geoscience Solutions for Sustainable Offshore Wind Development - A. P. M. Velenturf; A. R. Emery; D. M. Hodgson; N. L. M. Barlow; A. M. Mohtaj Khorasani; J. Van Alstine; E. L. Peterson; S. Piazolo; M. Thorp (Earth Science, Systems and Society)
Low carbon energy infrastructure, such as wind and solar farms, are crucial for reducing greenhouse gas emissions and limiting global temperature rise to 1.5°C. During 2020, 5.2 GW of offshore wind capacity went into operation worldwide, taking the total operational capacity of global offshore wind to 32.5 GW from 162 offshore windfarms, and over 200 GW of new capacity is planned by 2030. To meet net-zero targets, growth of offshore wind generation is expected, which raises new challenges, including integration of offshore wind into the natural environment and the wider energy system, throughout the wind farm lifecycle. This review examines the role of geosciences in addressing these challenges; technical sustainability challenges and opportunities are reviewed, filtered according to global governance priorities, and assessed according to the role that geoscience can play in providing solutions. We find that geoscience solutions play key roles in sustainable offshore wind energy development through two broad themes: 1) windfarm and infrastructure site conditions, and 2) infrastructure for transmission, conversion and energy storage. To conclude, we recommend priorities and approaches that will support geoscience contributions to offshore wind, and ultimately enable sustainable offshore wind development. Recommendations include industry collaboration and systems for effective data sharing and archiving, as well as further research, education and skills.